2016
DOI: 10.1016/j.eurpsy.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, migration stressors and suicidal ideation among Latino immigrants in Spain and the United States

Abstract: Background Immigration stress appears to augment the risk for suicide behaviors for Latinos. Yet, specific risk factors that contribute to suicidal ideation (SI) among diverse Latino immigrant populations are not well established. Methods Data were collected in Boston, Madrid and Barcelona using a screening battery assessing mental health, substance abuse risk, trauma exposure, demographics, and socio-cultural factors. Prevalence rates of lifetime and 30-day SI were compared across sites. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 63 publications
2
51
3
3
Order By: Relevance
“…Findings from this study indicate high rates of suicidal behaviors among the domestic rural migrants in China than the international immigrants in many developed countries (22). Although reversed findings are reported in a few studies (22).…”
Section: Characteristics Of the Suicidal Behaviors Among Chinese Ruracontrasting
confidence: 50%
“…Findings from this study indicate high rates of suicidal behaviors among the domestic rural migrants in China than the international immigrants in many developed countries (22). Although reversed findings are reported in a few studies (22).…”
Section: Characteristics Of the Suicidal Behaviors Among Chinese Ruracontrasting
confidence: 50%
“…As acculturation is associated with adaptation to stress (Caplan, 2007), current research has shifted focus to acculturative stress as a risk factor contributing to mental health disorders (Chae, Park, & Kang, 2014; Fortuna et al, 2016; Sirin, Ryce, Gupta, & Rogers-Sirin, 2013). According to the minority stress theory, experiencing stress due to marginalized status is associated with psychological distress (Meyer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The age distribution of the foreign resident population in Japan peaks at individuals in their twenties, which corresponds to an age of increased susceptibility to mental illnesses (Figure 1) [7,41,42]. Since immigrants are known to have greater mental vulnerability than the majority populations in a community [10,15,16,23], a number of foreign residents in Japan are thought to be at a high risk of mental illness.…”
Section: Distribution Of Foreign Patients According To Agementioning
confidence: 99%
“…Systematic reviews and meta-analyses have revealed that the incidence of psychotic disorders among immigrants and ethnic minority populations is about 1.5 to 3.0 times as high as that in ethnic majority populations [15]. Whereas a meta-analysis did not show a signi cant increase in mood disorders associated with immigration [22], immigrants who had been diagnosed as having depression were more likely to experience suicidal ideation [23]. Moreover, recent studies have shown that children and adolescents in immigrant families experience severe acculturative stress, which is associated with poor trajectories in mental health such as alcohol and substance use, eating disorders, and emotional and psychological problems [18,24].…”
mentioning
confidence: 99%